ETIKA TERHADAP HARTA DALAM PERSPEKTIF AL-QUR'AN - Ruston Nawawi (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
The title of this research is distributed by some of the statements in the Qur'an about ethics against the property. On the one hand the Qur'an looked positively treasure, on the other hand the Quran as if not condone. This research would like to find a concept of how the Qur'an against ethics against property by emphasizing the ethical discussion of acquiring property, possession and utilization of ethics of property. The type and pattern of this research is a library that is descriptive qualitative analysis. The main object of his research is the Qur'an. Therefore, the method used is the science of tafseer. Because this research is to find a concept, the approach used was thematic tafseer. The texts relating to the subject matter of discussion. As for to analyze the problem, the authors use think inductively, that is, seeks to provide answers to various issues of life with departure from nas Qur'an towards reality (min al-Qur'an ila al-waqi'. With this approach the authors limit themselves to things that are described by the Qur'an, including in the selection of the theme, and only use the vocabulary or term used Al Qur'an. The discussion in this paper are not directed to the type, quality or quantity of property. Instead it focused on the ethical attitude of man against the property, in which case the problem of acquiring property, possession and utilization of property. Of exposure data in this discussion, several conclusions, among them. The mention of the Qur'an on wealth seems less condone, not aimed at the material, melain aimed at human attitude towards wealth that made the property into a negative. The advice of the Qur'an against the wealth not only technical problems, but rather ethical issues as moral values built in Islam.